"Relaxing" incisions in abdominal surgery: Basic principies • surgical anatomy • patterns • types • indications. - Croci, Fabio; Pérez Penco, Ernesto (Cirugía del Uruguay, 1985)
" Among recourses for obliteralion of a parietal abdominal defect, parietal relaxing incisions have a role not ye! determined and usefulness not ye! well defined. They may be a myth or a physiopathological and biomechanic reality. Generally, what is sought by relaxing incisions is more the slipped eflect than the release of the tension on the edges of the opening to be closed. However, the use of same may be determined on the basis of strict concepts.